2020
DOI: 10.18502/fid.v16i5.2280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ozone and Two Common Denture Cleaners on Tensile Bond Strength and Surface Hardness of a Silicone Soft Liner

Abstract: Objectives: To evaluate the effect of ozone and two common denture cleansers on the surface hardness and bond strength of a silicone-based soft liner to acrylic denture base material. Materials and Methods: Sixty cylindrical specimens were fabricated using heat-cured poly-methyl methacrylate denture base resin. Three millimeters of the material was ground from the midsection and filled with the soft liner. The resilient liner specimens (n=40) used for the hardness test were 10 mm in diameter and 5 mm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Therefore, these observations might illustrate the lowering in bond strength of the acrylic soft liner in the present study after immersion in disinfectant solutions (Protefix cleansing tablet, 2% NaOCl, and 2% CHX) as compared to the control, and the bond strengths of these chemically different disinfectant groups were significantly different from each other. The findings from this study on the influence of NaOCl on tensile bond strength disagree with that of Nakhaei et al (2019) (14) when they considered that ozone and two commonly used denture cleaners (NaOCl and Corega tablets) had no effect on the adhesive strength of a silicone soft liner to acrylic denture base material. However, there are differences between the two studies in the type of soft liner, immersion period, and NaOCl solution concentration.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Therefore, these observations might illustrate the lowering in bond strength of the acrylic soft liner in the present study after immersion in disinfectant solutions (Protefix cleansing tablet, 2% NaOCl, and 2% CHX) as compared to the control, and the bond strengths of these chemically different disinfectant groups were significantly different from each other. The findings from this study on the influence of NaOCl on tensile bond strength disagree with that of Nakhaei et al (2019) (14) when they considered that ozone and two commonly used denture cleaners (NaOCl and Corega tablets) had no effect on the adhesive strength of a silicone soft liner to acrylic denture base material. However, there are differences between the two studies in the type of soft liner, immersion period, and NaOCl solution concentration.…”
Section: Discussioncontrasting
confidence: 85%
“…The Effect of 148 denture cleanser were delivered, and distilled water was altered every day (13,14).…”
Section: Various Disinfectionmentioning
confidence: 99%
“…16,17 There was no change in tensile strength after the exposure to ozonated water once, in accordance with previous studies. 18,31 Regarding the effects of exposure period, tensile strength decreased with the increase of the ozonated water immersion period.…”
Section: Discussionmentioning
confidence: 99%
“…15 Research revealed that the oral Grampositive and Gram-negative bacteria as well as Candida albicans were killed by immersion in ozonated water for one hour. 16 Another study by Arita et al, 17 showed that the use of ozonated water resulted in a decrease in Candida albicans counts Nakhaei et al, 18 evaluated the effect of ozone and two common denture cleansers on the surface hardness and bond strength of a siliconebased soft liner to the acrylic denture base material. A few studies have reported on the effects of ozone on the mechanical properties of the denture, so the present research was carried to study the effects of ozonated water compared to the microwaving on the tensile strength of heat-cured resins in two periods of exposure (at 1 day and 7 days).…”
Section: Introductionmentioning
confidence: 99%
“…Estrela et al 26 observed that the addition of ozone to an ultrasonic cleaning system containing different experimental solutions resulted in antibacterial activity against Staphylococcus aureus . Nakhaei et al 27 investigated the effect of ozonated water and two common denture cleaners on the tensile bond strength and hardness of a silicone soft liner. They observed that ozonated water and cleansing tablets (Corega) have a lower effect on the hardness of soft denture liners than that of 0.5% NaOCl.…”
Section: Discussionmentioning
confidence: 99%